Kualitas Pelayanan Kartu Keluarga Di Bidang Pendaftaran Identitas Kependudukan Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Pulang Pisau: Quality of Family Card Service in the Field of Registration of Population Identity in the Department of Population and Civil Registration of Pulang Pisau Regency - Megawati, Indah; Prayogo, Erwin Dwi (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2016)
The purpose of this study was to determine the Quality of Family Card Services in the Registration of Population Identity in the Population and Civil Registration Service in Pulang Pisau District. The research used in this study was a qualitative descriptive study conducted at the Pulang Pisau District Population and Civil Registration Service specifically in the area of ​​Population. The data sources are through interviews and observations. Data analysis is done by organizing and describing it into units, synthesizing, arranging into patterns, choosing which ones are important and which will be studied, and making conclusions that can be told to others. The results showed that the quality of service provided by the Pulang Pisau District Population and Civil Registration Service was very good in terms of transparency carried out by utilizing socialization activities by giving the task of cadres to explain to the community and take advantage of technological advances, then the performance of officers in serving the community good enough, this is indicated by the role and function of each officer and the officer is responsible for their respective duties even though the officer is still lacking in terms of disciplinary time problems. But overall the service in making a Family Card is efficient and effective. In serving the community, the value of the officer’s politeness is quite good, but there still needs to be an increase in hospitality.